Sleep-Disordered Breathing in Children with Prader-Willi Syndrome in Relation to Growth Hormone Therapy Onset - Zimmermann, Maja; Laemmer, Constanze; Wölfle, Joachim; Fimmers, Rolf; Gohlke, Bettina (Hormone Research in Paediatrics, 2020)
Objective: The aim of this study was to consider sleep apnea in Prader-Willi syndrome (PWS) children depending on age at growth hormone (GH) therapy onset. Study Design: We analyzed longitudinally cardiorespiratory polygraphy of 62 PWS children (aged 0-2.5 years at baseline). Twenty-one children (Group A) started GH-therapy during and 41 children (Group B) after their first year of life. Data were acquired before, at 3 and 6 months, then 1.2, 2.2, and 3.2 years after GH onset. Outcomes were determined with the obstructive apnea hypopnea index (OAHI), central apnea index (CAI), oxygen desaturation index (ODI), and by measuring obstructive sleep apnea (OSA) and peripheral blood oxygen saturation (SpO2). Results: We observed no significant differences in OAHI, CAI, ODI, and SpO2 depending on treatment onset. At baseline, 5/21 patients (23.8%) in Group A versus 15/41 patients (36.6%) in Group B showed pathological sleep apnea (OAHI ≥1.5). Pathological OSA increased significantly in Group A during the first 3 months of therapy but dropped below baseline after 1 year in both groups. ODI changed during GH therapy in both groups (from 4.0 to 2.6 in Group A, and 3.6 to 1.6 in Group B; baseline to 3.2 years; p < 0.05). Conclusions: OSA in PWS children appears to develop independently of treatment onset. Treatment may therefore safely be initiated early but should be accompanied by regular sleep analysis.
CRIS-Team Scopus Importer:2020-07-10